Utility of 80‐MHz Ultrasound Biomicroscopy and Lacrimal Endoscopy in Chronic Lacrimal Canaliculitis. (9th January 2021) - Luo, Ban; Qi, Xin
Abstract : Lacrimal canaliculitis (LC) is a rare infection of lacrimal passage, which is usually late diagnosed or misdiagnosed. Traditional lacrimal system tests barely provide a clear and definite understanding of the pathological changes in lacrimal passage. We presented three patients with asymptomatic and atypical symptoms who were misdiagnosed and were eventually diagnosed with chronic LC with assistance of 80‐MHz ultrasound biomicroscopy (80‐MHz UBM) and lacrimal endoscopy. To our knowledge, the mutual assistance of above two techniques diagnosing LC has never been reported, it can provide better images and observations of the canaliculus from the inside out and can guide the differential diagnosis.